Technological Pedagogical and Content Knowledge (TPACK) Integration in Teaching Music : A Perception of High School Music Teacher - Cipta, Febbry; Sukmayadi, Yudi; Milyartini, Rita; Kholid, Dody Mohamad; Gunara, Sandie (Universitas Pendidikan Mandalika, 2024)
This study aims to describe the perceptions of TPACK integration among high school music teachers in Bandung, West Java province, Indonesia. This study used mixed-methods with a sequential explanatory design. The research subjects consist of 19 respondents. In the first phase, quantitative data were obtained through questionnaires and analyzed using descriptive and inferential statistical techniques. In the second phase, in an effort to explore the results of the questionnaire, qualitatively conducted interviews as well as observations. The findings of this study showed that integration of each TPACK domain in music teaching was perceived as high confidence. Each domain, from one to another, positively correlated with varied interpretations. Demographic characteristics, both gender and tenure, did not show contrasting differences in confidence. This perception is the impact of the teacher education process that has been experienced, involvement in a number of trainings that have been followed, support from stakeholders in the procurement and enrichment of educational and technological resources, and the dynamics of the times that force them to be adaptive and innovative towards technological developments.